The Practice of Religion & Its Influence on Hatuhaha Language Shift in Central Moluccas - da Costa, Romilda Arivina (PAROLE: Journal of Linguistics and Education, 2016)
By the trade and the spread of Islam, Malay language (BM) was introduced. Hatuhaha language (BHT) and Malay language (BM) were used based on their needs. When Portuguese and The Netherlands ruled there, Hatuhaha communities (HA) forced down from the mountain and occupied the coastal areas. The use of Hatuhaha language (BHT) began to be prohibited; especially in the Hulaliu village which have been Christianized. On the contrary, in the four villages which were not Christianized, Hatuhaha language (BHT) was limited use because they did not always have business with the colonial. Furthermore, religious fragmentation occurs gradually, and impacted sosiologically on the development of Hatuhaha language (BHT). This phenomenon is then examined by quantitative and qualitative approaches that utilize the library study method, observation, survey, and interview. The results showed that in addition to the factors of colonization and Christianization, religious practice in Hatuhaha community (HA) has given more significant impact on Hatuhaha language (BHT) shift. It could be shown through correlation test by using Chi-Square on the level of frequency in using Hatuhaha language (BHT) on the domain of family, religious, and custom.